Taxonomic remarks, phylogeny and evolutionary notes on the leaf beetle species belonging to the Cryptocephalus sericeus complex (Coleoptera: Chrysomelidae: Cryptocephalinae) - Sassi, Davide (Zootaxa, 2014)
A cladistic analysis was carried out for a complex of 33 species of the genus Cryptocephalus that has been recognized for some time as monophyletic. 55 morphological adult characters have been used, with 119 character states. Analyses were performed using parsimony procedures as well as Bayesian inference. Further information about phylogenetic scenarios were obtained by combining the morphological dataset with a sequence of 507 bp of the central portion of the 18S ribosomal RNA. Illustrations are provided for most morphological characters used in the analyses. Besides, the following taxonomic changes are proposed here: subg. Cerodens has to be considered a new synonym of subg. Cryptocephalus; C. zambanellus is raised again to species level; C. sericeus intrusus has to be considered a new synonym of C. zambanellus; C. telueticus has to be considered a new synonym of C. azurescens; all the populations of C. violaceus ranging from Iberian Peninsula to central Alps are attributed to the subspecies scaffaiolus Burlini, formerly described from the Northern Apennines. Biogeographic remarks are given and some evolutionary hypotheses about the radiation of the monophylum are proposed on the basis of the acquired knowledge. An identification key for the species is also provided.